Southeast Asia in World History - Lockard, Craig A. (Oxford Oxford University Press, 2009)
This book will sketch an outline of Southeast Asian history from earliest times to the present, showing how the diverse political, economic, social, and cultural patterns developed over several thousand years and the role played by the region in the lar
Keywords: History - South East Asia